AutDB: a platform to decode the genetic architecture of autism. Issue Volume 46:Issue D1(2018) (25th November 2017) - Pereanu, Wayne; Larsen, Eric C; Das, Ishita; Estévez, Marcel A; Sarkar, Anjali A; Spring-Pearson, Senanu; Kollu, Ravi; Basu, Saumyendra N; Banerjee-Basu, Sharmila
Abstract: AutDB is a deeply annotated resource for exploring the impact of genetic variations associated with autism spectrum disorders (ASD). First released in 2007, AutDB has evolved into a multi-modular resource of diverse types of genetic and functional evidence related to ASD. Current modules include: Human Gene, which annotates all ASD-linked genes and their variants; Animal Model, which catalogs behavioral, anatomical and physiological data from rodent models of ASD; Protein Interaction (PIN), which builds interactomes from direct relationships of protein products of ASD genes; and Copy Number Variant (CNV), which catalogs deletions and duplications of chromosomal loci identified in ASD. A multilevel data-integration strategy is utilized to connect the ASD genes to the components of the other modules. All information in this resource is manually curated by expert scientists from primary scientific publications and is referenced to source articles. AutDB is actively maintained with a rigorous quarterly data release schedule. As of June 2017, AutDB contains detailed annotations for 910 genes, 2197 CNV loci, 1060 rodent models and 38 296 PINs. With its widespread use by the research community, AutDB serves as a reference resource for analysis of large datasets, accelerating ASD research and potentially leading to targeted drug treatments. AutDB is available at http://autism.mindspec.org/autdb/Welcome.do.